Stent retriever thrombectomy of small caliber intracranial vessels using pREset LITE: safety and efficacy - Kurre, Wiebke; Bäzner, Hansjörg (Clinical neuroradiology, 2017)
PurposeFew devices are approved for thrombectomy of distal vessel branches, and clinical experience is limited. Here we report our experience with pREset LITE for thrombectomy of small intracranial vessels.MethodsFrom an institutional database we selected consecutive patients treated with pREset LITE for an occlusion of small (≤ 2 mm), intracranial target vessels. Recanalization success was measured by applying the modified Thrombolysis In Cerebral Infarction (mTICI) score. To assess safety, we recorded device-related procedural events and potentially device-related hemorrhages on follow-up imaging. Infarcts in the dependent territory served as a measure for efficacy.ResultsOf 536 patients treated between August 2013 and March 2015, 76 met the inclusion criteria. pREset LITE was used in 90 branches with an average diameter of 1.6 mm (1.3-2.0 mm). An mTICI score ≥ 2b was achieved in 70.0 %. Procedural events consisted of 5.6 % significant vasospasm, 2.2 % suspected dissections, 2.2 % downstream emboli, and 1.1 % self-limiting extravasations. On posttreatment imaging 2.2 % parenchymal hemorrhages type I (PHI) and 13.3 % focal subarachnoid hemorrhage (SAH) were potentially device related, but all of these events remained asymptomatic. After successful recanalization, 33.3 % developed no ischemia in the dependent territory while 41.7 % developed a partial infarct, and 25 % developed a complete infarct. Successful recanalization significantly increased the chance to develop no or only partial infarct compared with a complete infarction (p = 0.003, p = 0.013).ConclusionsThrombectomy of small vessels with pREset LITE is feasible with good recanalization and reasonable safety margins. Successful recanalization significantly reduces the risk of infarction in the dependent territory. The impact on the overall clinical outcome remains to be determined.